PROSPEK KONSUMSI DAN IMPOR KEDELAI DI INDONESIA TAHUN 2015 - 2020 - Aimon, Hasdi; Satrianto, Alpon (Jurnal Kajian Ekonomi, 2014)
This study aims to analyze the influence of soybean import, per capita income, and soybean price to soybean consumption and to analyze prospect of soybean consumption in Indonesia from 2015 - 2020. Furthermore, the aim is also to analyze the influence of soybean consumption, per capita income and real exchange rate to soybean import and the prospect of soybean import in Indonesia from 2015 - 2020. The data used is from the time series 1983 until 2012. The analysis model in this study uses Ordinary Least Square (OLS) and Forecasting Vektor Autoregression (VAR). The result shows with OLS at soybean consumption equation that soybean import, per capita income, and soybean price significantly effects on the soybean consumption in Indonesia and it’s prospect with forecasting VAR shows that soybean consumption always increasing from 2015 - 2020. Moreover, soybean consumption, per capita income, and the real exchange rate significantly effect on soybean import in Indonesia and it’s prospect with forecasting VAR shows that soybean import always increasing from 2015 - 2020. The Soybean import values larger than soybean consumption values from 2018 - 2020. Accordingly, the recommends to the Indonesian government to reduce soybean imports by increasing soybean production by establishing local soybean prices, so that soybean farmers feel advantaged. Key Word: soybean consumption, soybean import, and soybean price.